Los barrios incas en el Cusco del siglo XVI y el Inca Garcilaso de la Vega: Un estudio de toponimia - Tord Velasco, Lorena (Pontificia Universidad Católica del Perú, 2024)
This article presents the initial findings of a toponymy study based on the chronicles of Inca Garcilaso de la Vega concerning the Inca neighborhoods of the city of Cusco. Garcilaso recorded twenty names of Inca neighborhoods that, according to the chronicler, were still in use during his residence in Cusco between 1539 and 1560. The documentation of these names has enabled us to conduct a thorough search in the historical archives of Cusco, Lima and Seville. Based on these results, we can assert that these names did indeed exist and remained in use among the residents of Cusco throughout the entire Viceroyalty period.

Este artículo presenta los primeros resultados de un estudio de toponimia basado en las crónicas del Inca Garcilaso de la Vega sobre los nombres de los barrios incas de la ciudad de Cusco. Garcilaso registró veinte nombres de barrios incas cusqueños que, según el cronista, eran nombres que continuaban en uso durante su residencia en Cusco entre los años 1539 y 1560. Hemos realizado una exhaustiva búsqueda de estos nombres de barrios incas en los archivos históricos de Cusco, Lima y Sevilla. Los resultados corroboran que estos nombres de barrios efectivamente existieron en el siglo XVI y que continuaron usándose durante todo el Virreinato.
The Inca neighborhoods of 16th-Century Cusco in the chronicles of Inca Garcilaso de la Vega: A toponymic study
Keywords: Cusco; Toponymy; Inca Garcilaso de la Vega; Neighborhoods; Colonial period; Viceroyalty; Urbanism; Ethnohistory; Cusco; Toponimia; Inca Garcilaso de la Vega; Barrios; Cusco colonial; Virreinato; Urbanismo; Etnohistoria; https://purl.org/pe-repo/ocde/ford#6.01.01